2018
DOI: 10.1158/0008-5472.can-17-3883
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes in the Premetastatic Niche

Abstract: The premetastatic niche formed by primary tumor-derived molecules contributes to fixation of cancer metastasis. The design of efficient therapies is limited by the current lack of knowledge about the details of cellular and molecular mechanisms involved in the premetastatic niche formation. Recently, the role of pericytes in the premetastatic niche formation and lung metastatic tropism was explored by using state-of-the-art techniques, including lineage-tracing and mice with pericyte-specific KLF4 deletion. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 116 publications
0
47
0
1
Order By: Relevance
“…The importance of the stroma was first recognized more than a century ago, beginning with observations that certain cancers metastasize exclusively to specific organs 1 . During the past two decades numerous studies have revealed interactions between malignant cells and the stroma that promote diverse tumor functions including angiogenesis 4,5 , metastasis 6 , and immunosuppression 7,8 . Stromal cells differ between patients and tumor types [9][10][11][12][13][14][15] and the abundance of certain stromal cell populations are used in the clinic as biomarkers [16][17][18][19] and therapeutic targets [20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the stroma was first recognized more than a century ago, beginning with observations that certain cancers metastasize exclusively to specific organs 1 . During the past two decades numerous studies have revealed interactions between malignant cells and the stroma that promote diverse tumor functions including angiogenesis 4,5 , metastasis 6 , and immunosuppression 7,8 . Stromal cells differ between patients and tumor types [9][10][11][12][13][14][15] and the abundance of certain stromal cell populations are used in the clinic as biomarkers [16][17][18][19] and therapeutic targets [20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some findings support the possibility of epithelial-pericyte transition occurring within the TME to support tumor processes such as angiogenesis [29]. Overall, research into cancer-associated pericytes remains limited, but given their role in normal tissue and noncancer diseases, and the importance of angiogenesis in tumorigenesis and progression, a better understanding will likely improve TME targeting strategies [29,30].…”
Section: Epithelial Cell Typesmentioning
confidence: 96%
“…The use of typical knockout mice models has proved useful in understanding the role of key molecules in physiological and pathological conditions . Nonetheless, these technologies have their limitations.…”
Section: Perspectives/future Directionsmentioning
confidence: 99%
“…However, this model is not yet available commercially, and those mice should be created in the future. In addition to studies using genetic mouse models, transcriptomic and single‐cell analyses represent fundamental tools that will help us understand the roles of macrophages within the skin healing microenvironment. These studies may be carried out by isolating via flow cytometry macrophages’ subpopulations from the skin before, and, at different time points, after lesion from both mice and humans.…”
Section: Perspectives/future Directionsmentioning
confidence: 99%